2016
DOI: 10.1016/j.xphs.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Converts Immunogenic Recombinant Human Acid Alpha-Glucosidase to a Tolerogenic Form in a Mouse Model of Pompe Disease

Abstract: Development of unwanted immune responses against therapeutic proteins is a major clinical complication. Recently, we have shown that exposure of Factor VIII (FVIII) in the presence of phosphatidylserine (PS) induces antigen-specific hypo-responsiveness to FVIII re-challenge, suggesting that PS is not immune suppressive, but rather immune regulatory in that PS converts an immunogen to a tolerogen. Since PS is exposed in the outer leaflet during apoptosis, we hypothesize that PS imparts tolerogenic activity to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…Moreover, PS-containing liposomes neither directly inhibited DC maturation in vitro in response to different stimuli, nor prevented DC migration to dLNs in vivo, hinting the complicated interactions among various immunocytes involved in the suppressive process sponsored by PS. Recently, Balu-lyer's group prepared Factor VIII-loaded liposomes with PS/PC (3:7 mol ratio), which when incubated with DCs in vitro caused increased secretion of TGF-β, and, when immunized to mice, due to PS incorporation, not only lowered the Ag-specific Ab response but also induced the hypo-responsiveness to the Ag re-challenge [96]. These outcomes suggest that PS-containing liposomes may function to exert the immune regulatory effects capable of converting an immunogen to a tolerogen, opposing the use as a VADS against pathogens.…”
Section: Surface Propertymentioning
confidence: 99%
“…Moreover, PS-containing liposomes neither directly inhibited DC maturation in vitro in response to different stimuli, nor prevented DC migration to dLNs in vivo, hinting the complicated interactions among various immunocytes involved in the suppressive process sponsored by PS. Recently, Balu-lyer's group prepared Factor VIII-loaded liposomes with PS/PC (3:7 mol ratio), which when incubated with DCs in vitro caused increased secretion of TGF-β, and, when immunized to mice, due to PS incorporation, not only lowered the Ag-specific Ab response but also induced the hypo-responsiveness to the Ag re-challenge [96]. These outcomes suggest that PS-containing liposomes may function to exert the immune regulatory effects capable of converting an immunogen to a tolerogen, opposing the use as a VADS against pathogens.…”
Section: Surface Propertymentioning
confidence: 99%
“…A similar approach was demonstrated with alpha-glucosidase (GAA) in a mouse model of Pompe disease. Administration of GAA-containing PS liposomes provided therapeutically active enzyme while preventing the formation of inhibitory antibodies ( 56 ). In an autoimmune setting, PS liposomes loaded with disease-relevant peptides were protective in the NOD animal model of T1D ( 54 ) and PLGA nanoparticles displaying PS and containing peptide autoantigens (from myelin oligodendrocyte protein, MOG 35–55 ) were also efficacious in an acute model of EAE (in B6 mice) ( 55 ).…”
Section: Tolerogenic Nps That Provide Antigen Alone To Harness Naturamentioning
confidence: 99%
“…Upon cellular apoptosis, PS flips to the outer membrane and acts as an "eat me" signal to phagocytic cells that engulf and digest cellular debris without the initiation of an immune response. We have shown that coadministration of PS with various therapeutic proteins and antigens (including rhGAA, FVIII and ovalbumin) can induce durable tolerance and prevent the development of antibodies 78,126 (unpublished data). Additionally, we have shown this method to be antigen specific, as rechallenge with an unrelated antigen showed a robust immune response 31 .…”
Section: Immune Tolerance Inductionmentioning
confidence: 91%
“…e) ELISA: ELISAs can also be used to detect ADA by coating the plate with the protein and incubating samples to measure ADA bound to the plate. This method has been used in our lab in conjunction with the Frey method to measure anti-rhGAA antibodies 78,79 . The utility of ELISAs can be limited because standards are not available for all ADA.…”
Section: D) Drug Tolerant Assaysmentioning
confidence: 99%
See 1 more Smart Citation